Soybean hulls inclusion on silage of wet brewery waste - Ana Rebeca Pires da Silva; Fabio Jacobs Dias; Ewerton de Souza Tanaka; Maycom Marinho Lopes; Rodrigo Rener dos Santos Martins; João Paulo Ferreira Rufino (Acta Scientiarum. Animal Sciences, 2021)
This study aimed to evaluate the effects of soybean hulls inclusion in the silage of wet brewery waste. The experimental design was randomized in block, where the treatments were constituted by four levels of soybean hulls on the silage (0, 15, 25, and 35%), with three (silos) replicates per treatment. All data collected were subjected to ANOVA and subsequent polynomial regression at 5%. Soybean hulls inclusion caused a linear increase (p < 0.05) in the pH, dry matter, acid detergent fiber, neutral detergent fiber and total carbohydrates content of the silage. This inclusion also caused a significant reduction (p < 0.05) in the effluent losses and percentages of crude protein, fats, hemicellulose, non-fibrous carbohydrates and total digestible nutrients. Thus, it was concluded that soybean hulls can be used as an additive in the silage of wet brewery waste. Up to 35% of inclusion, there was a significant reduction in the effluent losses, a little increase on pH and enrichment of nutritional content, especially in the dry matter.